Enhancing collaborative filtering tag-based recommendation with neural network model / Nurkhairizan Khairudin ... [et al.] - Khairudin, Nurkhairizan; Mohd Sharef, Nurfadhlina; Masrom, Suraya; Mustapha, Norwati; Mohd Noah, Shahrul Azman (Universiti Teknologi MARA, Perak, 2018)
Social tagging becomes more significant when the use of these tags can benefit the searching and browsing capabilities. In the recommendation systems, the use of information such as tags can improve the accuracy of the traditional recommendation by considering social interests and social trusts between users. However, sparsity is one of the major problems in tag-based recommendation system because users do not always want to volunteer to contribute tags because it not compulsory. Therefore, this research proposes a neural network tag-based recommendation that makes used of available tags to further support relationships with properties of items and users. The evaluation experiments show that the proposed approach improves the recommendation quality.